Phase-Shifted Pulse Width Modulation with Alternate Zeros Voltage for Parallel Connection of H-Bridges for High-Current Low-Voltage Applications - Rojas-Lobos, F; Diaz-Diaz, M; Verdugo-Naranjo, D; Lillo-Cartes, J (IEEE Computer Society, 2019)
Ahstract-Phase-Shifted Modulation (PSM) applied to multilevel converters is an effective method for reducing the output THD. In this paper, a new unipolar PSM method is proposed to control internal circulating current of a high-current low-voltage power converter, composed of parallel connected H- Bridges. The proposed method reduces the H-bridge currents distortions and the power losses of the overall converter. Simulation results comparing the standard unipolar modulation with the proposed unipolar modulation technique are performed to demonstrate its effectiveness. © 2019 IEEE.